THE INFLUENCE OF THE MARKETING MIX (7P) ON CONSUMER PURCHASING DECISIONS (CASE STUDY KUTARADJA FRIED CHICKEN DARUSSALAM) - Linda Santri; Nova Suryani (RADJA PUBLIKA, 2025)
This study analyzes how the 7P marketing mix (product, price, place, promotion, people, process, and physical evidence) influences purchasing decisions at Kutaradja Fried Chicken Darussalam. Using a quantitative approach, data were collected from 100 customers via questionnaires and analyzed through regression and hypothesis testing. Results showed that price, promotion, and physical evidence individually affected purchasing decisions (p < 0.05), while product, place, people, and process did not. However, all seven factors together significantly influenced decisions, explaining 66.4% of the variation (R² = 0.664). The findings suggest that competitive pricing, strong promotions, and appealing physical evidence are crucial for attracting customers. Although some elements lacked individual impact, their combined effect highlights the need for an integrated strategy. Kutaradja Fried Chicken should prioritize pricing, promotions, and store ambiance while maintaining balance across all 7Ps. This study offers practical insights for local fast-food businesses to strengthen marketing effectiveness.